2006
DOI: 10.1126/science.1127121
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Divalent Metal Ion Transporter CorA at 2.9 Angstrom Resolution

Abstract: CorA family members are ubiquitously distributed transporters of divalent metal cations and are considered to be the primary Mg2+ transporter of Bacteria and Archaea. We have determined a 2.9 angstrom resolution structure of CorA from Thermotoga maritima that reveals a pentameric cone-shaped protein. Two potential regulatory metal binding sites are found in the N-terminal domain that bind both Mg2+ and Co2+. The structure of CorA supports an efflux system involving dehydration and rehydration of divalent metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
238
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(252 citation statements)
references
References 25 publications
14
238
0
Order By: Relevance
“…12,25 The motif is located between two transmembrane ahelices on the outer surface of the membrane and it tends to be disordered in the crystal structures. [1][2][3] The mechanism of the ion selectivity for ZntB as a cation exporter has never been clear and it is not obvious why the metal ion needs to cross the entire pore to be selected for passage. While possible Mg 2þ gating mechanisms through the transmembrane were discussed in the Tm-CorA structures, 1-3 N314 residue at the external entrance to the pore and a pair of hydrophobic rings formed by M291 and L294, respectively, seemed to play important roles in selecting ion size and possible ion dehydration/rehydration steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,25 The motif is located between two transmembrane ahelices on the outer surface of the membrane and it tends to be disordered in the crystal structures. [1][2][3] The mechanism of the ion selectivity for ZntB as a cation exporter has never been clear and it is not obvious why the metal ion needs to cross the entire pore to be selected for passage. While possible Mg 2þ gating mechanisms through the transmembrane were discussed in the Tm-CorA structures, 1-3 N314 residue at the external entrance to the pore and a pair of hydrophobic rings formed by M291 and L294, respectively, seemed to play important roles in selecting ion size and possible ion dehydration/rehydration steps.…”
Section: Discussionmentioning
confidence: 99%
“…The three recently determined full-length Thermatoga maritima CorA (Tm-CorA) lower resolution structures (2.9, 3.7, and 3.9 Å) have revealed a striking homopentamer with two transmembrane a-helical spanners per monomer and a large funnel-shaped intracellular assembly. [1][2][3] However, two structures of cytoplasmic domains of Tm-CorA (1.85 Å) 1 and Archaeoglobus fulgidus CorA (Af-CorA) (2.9 Å) 3 showed dimeric arrangements of the CorA subunits. The observed conformational differences between the full-length TmCorA pentamer and the Af-CorA intracellular domain dimer were used to propose a close/open CorA translocation cycle model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been established whether Co 2+ enters mammalian cells via a specific transporter. In primitive organisms (bacteria, yeast) there are some specific transporters for the uptake and release of Co ions (Eitinger et al 2005, Eshaghi et al 2006. Such systems have not yet been shown to exist in mammalian cells.…”
Section: Metal Ions In Cellsmentioning
confidence: 99%
“…There is an absolutely conserved GMN motif near the end of the first hydrophobic region, and mutagenesis of CorA has shown that these three conserved residues are essential for functional Mg 2+ transport [14]. Recently, crystal structure of the pentameric cone-shaped CorA Mg 2+ transporter from Thermotoga maritima had been elucidated by several research groups [15][16][17][18], demonstrating CorA as a channel-like transport system. npg Li et al [12] and Schock et al [13] independently identified a 10-member Arabidopsis AtMGT gene family encoding Mg 2+ transport proteins that are homologous to the bacterial CorA.…”
Section: Introductionmentioning
confidence: 99%